2012
DOI: 10.1111/age.12002
|View full text |Cite
|
Sign up to set email alerts
|

Tandem repeats modify the structure of the canine CD1D gene

Abstract: SummaryAmong the CD1 proteins that present lipid antigens to T cells, CD1d is the only one that stimulates a population of T cells with an invariant T-cell receptor known as NKT cells. Sequencing of a 722 nucleotide gap in the dog (Canis lupus familiaris) genome revealed that the canine CD1D gene lacks a sequence homologous to exon 2 of human CD1D, coding for the start codon and signal peptide. Also, the canine CD1D gene contains three different short tandem repeats that disrupt the expected gene structure. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Although comparison of the CD1d coding sequences among a number of mammals indicates a relatively high level of evolutionary conservation, recent data suggest the CD1d gene is not fully functional in all species. For example, one recent report indicates that the CD1d gene in dogs lacks exons 2 and 3, and is therefore predicted to be non-functional (44). It has also been reported that many ruminants share a mutation that disrupts the normal CD1d start codon (4547).…”
Section: Discussionmentioning
confidence: 99%
“…Although comparison of the CD1d coding sequences among a number of mammals indicates a relatively high level of evolutionary conservation, recent data suggest the CD1d gene is not fully functional in all species. For example, one recent report indicates that the CD1d gene in dogs lacks exons 2 and 3, and is therefore predicted to be non-functional (44). It has also been reported that many ruminants share a mutation that disrupts the normal CD1d start codon (4547).…”
Section: Discussionmentioning
confidence: 99%
“…The canine locus on the other hand is much larger than the human locus. It has 4 functional CD1a genes and 5 CD1a pseudogenes, and furthermore there is 1 gene of each of the other isoforms [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%